PERAN DAN UPAYA GURU DALAM PEMBENTUKAN KARAKTER KEDISIPLINAN PADA SISWA KELAS IV SDN 6 WATAMPONE KECAMATAN TANETE RIATTANG KABUPATEN BONE - Jafar, Muhammad Idris; Rahmi, Sitti; Sulistiani (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
This study is a qualitative study with a qualitative descriptive approach that aims to determine the role and efforts of teachers in the formation of disciplined character in fourth grade students. Descriptive qualitative study of fourth grade students of SDN 6 Watampone, Tanete Riattang District, Bone Regency. Research data were obtained through interviews and documentation. Data analysis techniques are data reduction, data presentation, and drawing conclusions. The results of this study indicate that the role of teachers in the formation of disciplined character in fourth grade students is very important and holistic. Teachers do not only serve as educators who instill disciplined values ​​through learning, but also as mentors, trainers, and evaluators who actively shape, guide, and evaluate students' disciplined behavior. Teachers' efforts in the formation of disciplined character in fourth grade students are carried out holistically and integratedly. Teachers do not only rely on setting rules through class agreements, but also teach time management, provide supportive guidance, and exemplify disciplined behavior in everyday life. This holistic and integrated approach is supported by open communication, cooperation with parents, and family problem solving, so that students can internalize and apply disciplined values ​​consistently in various aspects of their lives.